2021
DOI: 10.3233/jpd-202428
|View full text |Cite
|
Sign up to set email alerts
|

Digital Progression Biomarkers as Novel Endpoints in Clinical Trials: A Multistakeholder Perspective

Abstract: The burden of Parkinson’s disease (PD) continues to grow at an unsustainable pace particularly given that it now represents the fastest growing brain disease. Despite seminal discoveries in genetics and pathogenesis, people living with PD oftentimes wait years to obtain an accurate diagnosis and have no way to know their own prognostic fate once they do learn they have the disease. Currently, there is no objective biomarker to measure the onset, progression, and severity of PD along the disease continuum. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
(27 reference statements)
0
32
0
Order By: Relevance
“…Sensor-based remote monitoring could also help increase representation for groups whose data have historically not been included in clinical trials 9 , 10 . Before such measurements can be used as endpoints in clinical trials to quantify disease progression, a careful evaluation of the clinical validity, reliability, and sensitivity to change is required 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Sensor-based remote monitoring could also help increase representation for groups whose data have historically not been included in clinical trials 9 , 10 . Before such measurements can be used as endpoints in clinical trials to quantify disease progression, a careful evaluation of the clinical validity, reliability, and sensitivity to change is required 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…30 Data quality of data generated by decentralized means It has been suggested that digital technologies could lead to more clinically meaningful end points than conventional end points, as data could be collected more frequently, and more objectively due to the reduced impact of observer and recall bias. 31,32 Although the opportunity to collect richer data via digital technologies was recognized by the regulators, they were cautious about the impact of large data sets on end points. In addition, missing data due to technical defects or poor technology adherence were found to be a potential challenge.…”
Section: Justification Of Decentralized Elementsmentioning
confidence: 99%
“…This approach, however, does not include additional important measures, such as monitoring a patient in their home, work, or social environment, which can provide insight into the patient's lived experience 9 with much more relevance than snapshots of their condition that is garnered at intermittent clinical visits. Wearable technology has the potential to provide such information, particularly as it relates to motor symptoms, gait, functional mobility, falls, and tremor, but limitations in assessing nonmotor symptoms and lack of standardized measurements that may be used universally in the clinical and research arenas are problematic 10 …”
Section: The Search For a Universal Outcome Measurementioning
confidence: 99%
“…Wearable technology has the potential to provide such information, particularly as it relates to motor symptoms, gait, functional mobility, falls, and tremor, but limitations in assessing nonmotor symptoms and lack of standardized measurements that may be used universally in the clinical and research arenas are problematic. 10 What this consensus does reveal is that there is an extensive number of determinants of health for patients with PD, which can be complicated to measure. But there is a common thread: all these parameters, to differing degrees, ultimately affect a patient's quality of life, and perhaps this is, in fact, the most telling outcome measure.…”
Section: Lack Of a Universal Outcome Measurementioning
confidence: 99%